Experimental testing, numerical modelling and seismic strengthening of traditional stone masonry: comprehensive study of a real Azorian pier - Alexandre A. Costa (2012)
Stone masonry is one of the oldest building techniques used worldwide and it is known to exhibit poor behaviour under seismic excitations. In this context, this work aims at assessing the in-plane behaviour of an existing double-leaf stone masonry pier by experimental testing. Additionally, a detailed 3D finite element numerical analysis based on micro-modelling of the original pier is presented (fully describing the geometry and division of each individual elements, namely infill, blocks and joints) aiming at simulating the experimental test results. This numerical strategy can be seen as an alternative way of analysing this type of constructions, particularly useful for laboratory studies, and suitable for the calibration of simplified numerical models. As part of a wider research activity, this work is further complemented with the presentation of an effective retrofit/strengthening technique (reinforced connected plaster) to achieve a significant improvement of its in-plane cyclic response which is experimentally verified in the results presented herein.